Diet Drives Convergence in Gut Microbiome Functions Across Mammalian Phylogeny and Within Humans - Muegge, Brian D.; Kuczynski, Justin; Kinghts, Dan; Clemente, Jose C.; González, Antonio; Fontana, Luigi; Henrissat, Bernard; Knight, Rob; Gordon, Jeffrey I. (Science (American Association for the Advancement of Science), 2011)
Coevolution of mammals and their gut microbiota has profoundly affected their radiation into myriad habitats. We used shotgun sequencing of microbial community DNA and targeted sequencing of bacterial 16S ribosomal RNA genes to gain an understanding of how microbial communities adapt to extremes of diet. We sampled fecal DNA from 33 mammalian species and 18 humans who kept detailed diet records, and we found that the adaptation of the microbiota to diet is similar across different mammalian lineages. Functional repertoires of microbiome genes, such as those encoding carbohydrate-active enzymes and proteases, can be predicted from bacterial species assemblages. These results illustrate the value of characterizing vertebrate gut microbiomes to understand host evolutionary histories at a supraorganismal level.